Efeitos do treinamento físico sobre o metabolismo e expressão de proteínas inflamatórias em ratos com doença periodontal, diabéticos ou não - Andrade, Eric Francelino (2016)
Periodontal disease (PD) is a complication of diabetes mellitus (DM). A bidirectional relationship exists between these disorders. Once physical activity can improve metabolic and inflammatory status, the aim of this study was to investigate the effects of exercise on alveolar bone loss and anxious/depressive behavior in rats with PD. We also evaluated the metabolic profile of rats induced to PD and type 2 DM. This thesis was divided into three chapters. At first we performed a systematic review which investigated the effects of exercise on the progression of PD. Of the 24 selected articles, 12 observed that exercise attenuates the PD, while 10 found no difference and two reported worsening. In second study, 24 male Wistar rats were distributed in factorial design 2X2 (with or without DP, with or without exercise). The animals trained for eight weeks and DP was induced by ligature, at the last 14 days of the experiment. On the last week of experiment the anxious/depressive behavior was assessed. The data were submitted to analysis of variance (ANOVA) (p < 0,05). Exercise attenuated bone loss and anxious/depressive behavior, enhanced local inflammatory profile and increased branching of hippocampal astrocytes. In the third chapter, 40 rats were distributed in a factorial design 2x2x2 (induced or not to PD, diabetic or not, trained or not). Type 2 diabetes was induced by administration of high fat diet for four weeks associated with a low dose of streptozotocin (35 mg/kg of animal). During eight weeks animals were trained and 14 days before the end of the experiment, PD was induced by ligature. Data were submitted to ANOVA and means were compared by F test (p < 0,05). Trained diabetic animals exhibited lower bone loss (evaluated by morphometric analysis), blood glucose, glycated hemoglobin and triacylglycerols. No changes were observed in total cholesterol and fractions. We conclude that the training improves anxiety/depression, besides reducing inflammation and bone loss in rats with PD, diabetic or not.